An improved dq-frame wideband impedance identification method for power supply network with only one disturbance - Zhao, Changjun; Wei, Kai; Yan, Xing; Lin, Haojin (Frontiers in Energy Research, 2023)
To cope with the energy crisis and environmental degradation, the new energy represented by wind and photovoltaic power generations have developed rapidly, which leads to a large number of power electronic converters being connected to the power grid. In this context, the power-electronic-based power system has become a trend. However, when wideband impedance mismatch happens between the power electronic converter and the connected power supply network, the wideband oscillation will occur in the system, which seriously endangers the safe and stable operation of the power system. To solve it, impedance identification is a key step to obtain the dq-frame impedance characteristics to analyze the power system stability. This article focuses on the power supply network and proposes an improved method to identify its dq-frame wide-band impedance by only one disturbance, which greatly simplifies the dq-frame wideband impedance identification process to improve the identification efficiency. It is of great significance for the safe and stable operation of the power-electronic-based power system.